A review on cellulose nanocrystals as promising biocompounds for the synthesis of nanocomposite hydrogels. (15th July 2019) - Shojaeiarani, Jamileh; Bajwa, Dilpreet; Shirzadifar, Alimohammad
Highlights: The application of hydrogels containing CNCs are intensively studied. Specific studies on biomedical application of CNC hydrogels are described. Synthesis methods of hydrogels containing CNCs are covered. CNC hydrogels with high adsorption capacity to positive ions are reviewed. Abstract: Hydrogels are hydrophilic cross-linked polymer networks formed via the simple reaction of one or more monomers with the ability to retain a significant extent of water. Owing to an increased demand for environmentally friendly, biodegradable, and biocompatible products, cellulose nanocrystals (CNCs) with high hydrophilicity have emerged as a promising sustainable material for the formation of hydrogels. The cytocompatibility, swellability, and non-toxicity make CNC hydrogels of great interest in biomedical, biosensing, and wastewater treatment applications. There has been a considerable progress in the research of CNC hydrogels, as the number of scientific publications has exponentially increased (>600%) in the last five years. In this paper, recent progress in CNC hydrogels with particular emphasis on design, materials, and fabrication techniques to control hydrogel architecture, and advanced applications are discussed.